2011
DOI: 10.13101/ijece.4.32
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Assessing Deep Catastrophic Landslide Susceptibility

Abstract: In steep mountainous regions, deep catastrophic landslides that involve weathered bedrock as well as soils can cause serious damage. However, there is currently no widely used method for estimating spatial patterns of susceptibility to deep catastrophic landslides. We propose a new method to estimate landslide susceptibilities for many small catchments (~1 km 2) over relatively large areas (hundreds of square kilometers). Our method identifies catchments prone to deep catastrophic landslides according to three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…Deep-seated landslides have been reported since 70 years ago (Stini 1941), but the definition and understanding of these landslides remain difficult to clarify. Although typical characteristics and quantifiable definition of deep-seated landslides have been proposed, such as by Agliardi et al (2001) and Uchida et al (2011), it is still extremely difficult to predict where and when a deepseated landslide will occur. The characteristics of rainfall in Taiwan have been gradually changing to heavy rainfall with high intensity or long duration during recent years (Shiu et al 2009).…”
Section: Dam Failure and River Dischargementioning
confidence: 99%
“…Deep-seated landslides have been reported since 70 years ago (Stini 1941), but the definition and understanding of these landslides remain difficult to clarify. Although typical characteristics and quantifiable definition of deep-seated landslides have been proposed, such as by Agliardi et al (2001) and Uchida et al (2011), it is still extremely difficult to predict where and when a deepseated landslide will occur. The characteristics of rainfall in Taiwan have been gradually changing to heavy rainfall with high intensity or long duration during recent years (Shiu et al 2009).…”
Section: Dam Failure and River Dischargementioning
confidence: 99%
“…1 km 2 ) over relatively large areas (ca. hundreds of km 2 ) has been proposed [Tamura et al, 2008;Uchida et al, 2011]. Uchida et al [2011] successfully demonstrated the applicability of this method using data from Mount Wanitsuka, Japan, where deep catastrophic landslides occurred during a typhoon in 2005.…”
Section: Prefacementioning
confidence: 99%
“…hundreds of km 2 ) has been proposed [Tamura et al, 2008;Uchida et al, 2011]. Uchida et al [2011] successfully demonstrated the applicability of this method using data from Mount Wanitsuka, Japan, where deep catastrophic landslides occurred during a typhoon in 2005. Additionally, Takezawa et al [2012] confirmed the applicability of the method in a mountainous area around Mount Kurikoma, Japan, where a number of co-seismic deep-seated rapid landslides were triggered by an earthquake in 2008.…”
Section: Prefacementioning
confidence: 99%
See 1 more Smart Citation
“…In order to prepare for such landslide disasters, it is necessary to gain an understanding, in advance, of the locations and scales of landslides and deep-seated landslides that can result from earthquakes and heavy rainfall. Therefore, numerous studies on risk evaluation methods for slope failure have been conducted (Khasbaatar et al, 2009;Hayashi et al, 2011;Higaki et al, 2011;Uchida et al, 2011). Landslide and slope failure research is generally performed by conducting topographical and geological reconnaissance and boring…”
Section: Introductionmentioning
confidence: 99%